The Evolution of Balanced Scorecard as a Strategic Management Tool - Eftimov, Lјupcho; Trpeska, Marina (MIPRO Croatia, 2007)
Robert Kaplan and David Norton have been, and remained among the most influential authors in the field of Performance Management and their Balanced Scorecard still is the most successful concept in this field. This paper describes the evolution of Balanced Scorecard distinguishing three main evolution phases in its development, concerning the strategic and performance management literature. The paper examines the results of BSC implementation in the companies worldwide, and highlights potential areas for its improvement.
Keywords: performance measurement, balanced scorecard, strategy map